Efficacy and Safety of CD19-Targeted Chimeric Antigen Receptor (CAR) T-Cell Therapy in Refractory Systemic Lupus Erythematosus: A Systematic Review of Clinical Outcomes and B-Cell Depletion Kinetics - I Made Eryana; Ni Putu Ayu Windari Putri; Cokorda Agung Paramadika (HM Publisher, 2026)
Systemic lupus erythematosus (SLE) is a heterogeneous autoimmune pathology characterized by a breakdown in self-tolerance, B-cell hyperactivity, and the production of pathogenic autoantibodies. While conventional B-cell depletion strategies utilizing monoclonal antibodies often fail to achieve deep tissue clearance, CD19-targeted chimeric antigen receptor (CAR) T-cell therapy has emerged as a transformative modality capable of inducing durable drug-free remission. This systematic review and meta-analysis evaluate the clinical efficacy, pharmacodynamics of B-cell depletion, and safety profile of both autologous and allogeneic CD19 CAR T-cell therapies in refractory SLE. We conducted a systematic literature review on manuscripts published between January 1st, 2014, and March 1st, 2025, focusing on interventional clinical trials and high-quality case series. Primary endpoints included the Definition of Remission in SLE (DORIS) and reduction in SLEDAI-2K scores. Secondary endpoints analyzed B-cell aplasia kinetics, seroconversion of anti-dsDNA, and adverse events, including cytokine release syndrome (CRS), immune effector cell-associated neurotoxicity syndrome (ICANS), and novel autoimmune-specific toxicities. Statistical synthesis utilized weighted averages for continuous variables and event rates for categorical outcomes. The analysis synthesized data from 20 distinct patients with refractory SLE across three pivotal cohorts. The pooled rate of DORIS remission at three months post-infusion was 100%. The mean SLEDAI-2K score decreased from a baseline of 12.5 to 0.8 at three months. Deep B-cell depletion was achieved in all patients, with a mean duration of aplasia of 112 days. Reconstitution of the B-cell compartment was characterized by a naïve phenotype (IgD+/CD27-), indicating a comprehensive immunological reset. Safety analysis revealed that while CRS occurred in 88% of patients, it was predominantly Grade 1 or 2. No high-grade ICANS occurred. Unique toxicity signals, including local immune effector cell-associated toxicity syndrome (LICATS), were identified. In conclusion, CD19-targeted CAR T-cell therapy induces rapid, profound, and sustained drug-free remission in patients with refractory SLE. The mechanism involves deep tissue depletion of B-cells and plasmablasts, facilitating a reset of the humoral immune system.